Analysis of Implementation of the Concept of Quality Tourism Development Tourism in the Framework of Supporting Marketing Tourism Village - Pangestuti, Edriana; Supriono, Supriono; Bafadal, Aniesa; Fithriyah, Nabiila Rahayu (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study aims to analyze the implementation of the quality tourism concept in the development of Sidomulyo Tourism Village, East Java. Despite its potential as an alternative tourist destination, the application of quality tourism principles has not been fully optimized.Methodology: This research employs a descriptive qualitative method. Primary data were obtained through interviews and observations, while secondary data were collected from documents. The data analysis was conducted through four stages: data condensation, data presentation, and conclusion drawing.Findings: The study indicates that the development of Sidomulyo Tourism Village has been progressing well, particularly before the COVID-19 pandemic and the eruption of Mount Semeru. However, improvements are still needed, especially in infrastructure conditions. The implementation of quality tourism standards has begun but requires enhancement in safety and security, cleanliness, and accessibility.Conclusion: The application of the quality tourism concept in Sidomulyo Tourism Village is heading in a positive direction but remains suboptimal. Further improvements, particularly in infrastructure and service quality, are necessary to ensure sustainable tourism development.